Digital health literacy of adolescents: A scoping review protocol - Hannah Linney; Ken van Someren; Sinead Keogh (PLoS ONE, 2026)
Introduction Adolescence is a key developmental period in which new health behaviours are often initiated that track into adulthood. In the age of digitisation, adolescents are frequently exposed to and actively seek health information from digital sources. Widespread misinformation necessitates the ability to critically evaluate the reliability of sources, a key component of digital health literacy. Digital health literacy, sometimes called e-health literacy, is considered a determinant of health. Evidence suggests an association between digital health literacy and health behaviours among adults; however, the concept has been sparsely investigated among adolescents. This protocol outlines a proposed scoping review that aims to identify, map and synthesise the currently available literature relating to the digital health literacy of adolescents. Objective The objective of the proposed scoping review is to understand the extent, breadth and type of evidence available regarding the digital health literacy or e-health literacy of adolescents. Methods A scoping review of literature will be conducted in accordance with the methodological framework proposed by Arksey and O’Malley, with refinements suggested by Levac et al and guided by the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis. Reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR). Searches for relevant studies have been conducted across five electronic databases (PubMed, CINAHL, Web of Science, Education Source and Scopus). Title and abstract screening, which has commenced, will be conducted primarily by the lead reviewer, with independent verification of a subset of records to enhance rigour and minimise selection bias. This will be followed by full text screening using Covidence software. The PCC (Population, Concept and Context) framework guided the development of the inclusion and exclusion criteria for study selection. A manual search of references of included studies will be conducted to identify further studies for inclusion. Data will be extracted and analysed using a descriptive mapping approach. Inclusion criteria Published quantitative and qualitative studies exploring the digital health literacy, or e-health literacy of adolescents aged 10 to 19 years will be included. Eligible study designs include randomised controlled trials, non-randomised controlled trials, pre-post studies, prospective and retrospective cohort studies, case-control studies and analytical cross-sectional studies. This review will also consider descriptive observational study designs including case series, individual case reports and descriptive cross-sectional studies for inclusion. Discussion The proposed scoping review aims to map how digital health literacy is defined and measured among adolescents, providing greater conceptual clarity within the emerging field. By identifying patterns, inconsistencies, and gaps in the literature, the findings are expected to inform future research priorities, scale development, and the design of targeted interventions in educational and public health settings. Consistent with the scoping review methodology, a risk of bias assessment will not be conducted however the systematic approach will map the available evidence and form the basis for future research. This scoping review protocol has been preregistered on the Open Science Framework (OSF Registries, available at: https://osf.io/xsvpz/ ).